2008
DOI: 10.1093/humrep/den228
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mifepristone on breast cell proliferation in premenopausal women evaluated through fine needle aspiration cytology

Abstract: The ability of mifepristone to block breast epithelial cell proliferation in premenopausal women may prove beneficial when used for contraceptive purposes or for other gynaecological indications. Future studies should address a possible antiproliferative effect in the post-menopausal breast tissue during hormone replacement therapy. Our results implicate a possible protective effect of mifepristone on the breast epithelium. ClinicalTrials.gov NCT00579475.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 27 publications
0
30
0
2
Order By: Relevance
“…Furthermore, both MPA and P have been found to reactivate stem cells with potential for malignancy, in vitro, but the clinical implications of this finding for women are not elucidated (29). Recently we reported that so far the only antiproliferative drug in normal breast tissue in vivo is the anti-P mifepristone, which significantly reduced breast cell proliferation in premenopausal women (30).…”
mentioning
confidence: 99%
“…Furthermore, both MPA and P have been found to reactivate stem cells with potential for malignancy, in vitro, but the clinical implications of this finding for women are not elucidated (29). Recently we reported that so far the only antiproliferative drug in normal breast tissue in vivo is the anti-P mifepristone, which significantly reduced breast cell proliferation in premenopausal women (30).…”
mentioning
confidence: 99%
“…The inhibitory effect of CDB-4124 on cell proliferation we see in both, long-and short-term (3 month) treatments correlates well with recent data from a clinical trial with mifepristone (RU-486). Women with leiomyoma, treated with 50 mg RU-486 every second day for 3 months, underwent fine-needle breast biopsies before initiation and after termination of treatment (5). A significant reduction in proliferating breast epithelial cells (Ki-67-positive) were observed in RU-486-treated versus placebo-treated patients, suggesting that antiprogestin treatment can prevent the development and progression of ER þ and PR þ breast cancer by inhibiting MEC proliferation.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It is generally accepted that progesterone receptor (PR) is an estrogen-regulated gene and its synthesis in normal and tumor cells requires estrogen and estrogen receptor (ER; refs. 4,5). As a result of endocrine therapy with tamoxifen, ER and PR in breast cancer cells may decrease, but complete loss of receptor does not occur (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Women with leiomyoma treated with 50 mg of RU-486 every second day for 3 months underwent fine needle breast biopsies before initiation and after termination of treatment (Engman et al, 2008). A significant reduction in proliferating breast epithelial cells (Ki-67 positive) was observed in RU-486 treated vs. placebo treated patients, suggesting that antiprogestin treatment can prevent the development and progression of ER+ and PR+ breast cancer by inhibiting mammary epithelial cell proliferation.…”
Section: Cellular Mode Of Action: Mammary Proliferation and Apoptosismentioning
confidence: 99%